Hong Kong Med J 2020
DOI: 10.12809/hkmj208373
|View full text |Cite
|
Sign up to set email alerts
|

Burden of pneumococcal disease: 8-year retrospective analysis from a single centre in Hong Kong

Abstract: Streptococcus pneumoniae is a common pathogen involved in community-acquired pneumonia. Invasive pneumococcal disease is often associated with higher co-morbidity rates, but mortality-related findings have been inconclusive. This study investigated predictors of 30-day mortality and invasive pneumococcal disease. Methods: This retrospective analysis included adults with pneumococcal disease who were admitted to Pamela Youde Nethersole Eastern Hospital from 1 January 2011 to 31 December 2018. Demographics, micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The 26 articles were published between 2000 and 2020, reported from Spain and the United States (n = 3 each), Canada, Japan, Israel, South Korea, the Netherlands, the United Kingdom, and Taiwan (n = 2 each), and 6 other countries (n = 1 each) 6 , 12 36 . Two articles from Sweden and Georgia were multi-country studies compromising patients from 5 and 10 countries (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 26 articles were published between 2000 and 2020, reported from Spain and the United States (n = 3 each), Canada, Japan, Israel, South Korea, the Netherlands, the United Kingdom, and Taiwan (n = 2 each), and 6 other countries (n = 1 each) 6 , 12 36 . Two articles from Sweden and Georgia were multi-country studies compromising patients from 5 and 10 countries (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…По данным Всемирной организации здравоохранения (ВОЗ), инфекции нижних дыхательных путей, включая пневмонию, остаются самыми смертоносными инфекционными заболеваниями, от которых в 2015 г. в мире умерли 3,2 млн человек. Тяжесть и исход внебольничной пневмонии определяет и коморбидная патология, такая как хроническая обструктивная болезнь легких, сердечная недостаточность, цереброваскулярные заболевания, заболевания почек, метаболический синдром и сахарный диабет [2][3][4][5][6][7][8][9].…”
Section: Introductionunclassified
“…32 Another study found that clinicians who specialised in respiratory diseases, thoracic surgery, and cardiology were more committed to encouraging patients to cease tobacco use. 33 We believe that the study by Man et al 19 acts as a call for more active participation by physicians in disease prevention and screening programmes, and appeal for your support. Physicians play an important role in both primary and secondary disease prevention for asymptomatic individuals, including promotion of lifestyle modifications, vaccination for infectious diseases, and screening for early-stage cancer lesions such as cervical cancer and colorectal cancer.…”
mentioning
confidence: 96%
“…15 Other examples of Government-subsidised programmes for disease prevention include cervical cancer screening, 16 colorectal cancer screening, 17 and the Smoking Cessation Programme. 18 In this issue of the Hong Kong Medical Journal, Man et al 19 report an 8-year large-scale retrospective cohort study that included 792 adult patients in a major hospital. The authors found that the 30-day mortality rates were 11.5% overall and 24.5% in those patients with IPD.…”
mentioning
confidence: 99%